WAYS TO IMPROVE THE EFFICIENCY OF STATE FINANCIAL CONTROL BASED ON TAXPAYER SEGMENTATION AND RISK ANALYSIS SYSTEMS - Axmedov , Kamron (INTERNATIONAL CONFERENCE ON SCIENCE, INNOVATION AND GLOBAL DEVELOPMENT, 2026)
This thesis examines the role of taxpayer segmentation and risk-analysis mechanisms in enhancing the efficiency of state financial control, with a particular focus on tax administration. The study substantiates the need to shift from comprehensive control methods to a targeted approach that concentrates administrative resources on high-risk entities. The research includes a comparative analysis of practices recommended by international organizations (OECD, ISORA) and the experiences of advanced tax jurisdictions (IRS, SARS), juxtaposed with the regulatory framework and implementation of the risk management system in the Republic of Uzbekistan. Based on the findings, the thesis proposes priority directions for modernization, including the adoption of artificial intelligence and machine learning technologies, the development of differentiated control strategies per taxpayer segment, and the enhancement of inter-agency data integration.